A novel electronic paper display based on in-plane dielectrophoresis - Tng, Li Hui. (2013)
Since the success of the Amazon Kindle in 2009, electronic paper displays have become one source of great competition for the next major technological product breakthrough. Currently, majority of commercially-available e-book readers utilize electrophoretic displays which operate by moving charged particles using an electric field. This study explores an alternative approach to achieve an electronic paper display using the combined effect of negative dielectrophoresis (DEP) and dipole interactions. The formation of words is studied using polystyrene particles in a non-uniform AC electric field on a prototype display. Building upon previous investigations on the effect of particle size, inter-electrode gap, electric field frequency and applied voltage, this paper focuses on the effect of different concentrations of organic and electrolytic media on the response rate and transmittance of the dielectrophoretic electronic paper display. Ethanol and KCl were selected as the organic and electrolytic media respectively.